The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1021/acs.jchemed.3c00119
|View full text |Cite
|
Sign up to set email alerts
|

Escape the Desert Island: Blended Escape Rooms in the First-Semester Problem-Based Learning

Abstract: Educational escape rooms are immersive puzzlebased games that rely on teamwork skills in problem-solving, critical thinking, and communication. This paper describes the development of desert island themed escape rooms in a blended learning environment using physical and online puzzles that were hosted on Genially. The blended escape rooms were designed to introduce terms and concepts in pharmaceutical chemistry of drugs to first-year students while breaking the ice by fostering rapport, camaraderie, and teamwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Many researchers have developed games for chemical and biochemical education. Examples include card games to aid memorization, quiz games, , board games with chemical challenges, escape rooms, narrative games, , murder mysteries, , and the use of ChemDraw as a game . Game writing has been used as an educational tool, while Lego and Lego Serious Play have been used to teach scientific concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have developed games for chemical and biochemical education. Examples include card games to aid memorization, quiz games, , board games with chemical challenges, escape rooms, narrative games, , murder mysteries, , and the use of ChemDraw as a game . Game writing has been used as an educational tool, while Lego and Lego Serious Play have been used to teach scientific concepts.…”
Section: Introductionmentioning
confidence: 99%
“…20 To help pharmacy students learn the complex topic of stereochemistry, Abdul Rahim found that the students became more engaged when participating in online escape rooms to solve puzzles rather than listening to a traditional lecture. 16 Lopez-Pernas et al noted that while in-person and remote educational escape rooms improved students' knowledge in computer programming, in-person escape room participation yielded slightly higher postactivity test scores compared to the remote versions. 24 Interestingly, unlike the previous studies, another involved undergraduates designing their own digital escape rooms with peers in an introductory ecology course, leading to increased engagement.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similarly, Vergne and co-workers evaluated student understanding of fundamental organic chemistry in a chocolate factory themed digital escape room . To help pharmacy students learn the complex topic of stereochemistry, Abdul Rahim found that the students became more engaged when participating in online escape rooms to solve puzzles rather than listening to a traditional lecture . Lopez-Pernas et al noted that while in-person and remote educational escape rooms improved students’ knowledge in computer programming, in-person escape room participation yielded slightly higher postactivity test scores compared to the remote versions .…”
Section: Introductionmentioning
confidence: 99%